Cytologic features and clinical implications of undifferentiated carcinoma with osteoclastic giant cells of the pancreas: An analysis of 15 cases. Issue 7 (3rd April 2017) - Reid, Michelle D.; Muraki, Takashi; HooKim, Kim; Memis, Bahar; Graham, Rondell P.; Allende, Daniela; Shi, Jiaqi; Schaeffer, David F.; Singh, Remmi; Basturk, Olca; Adsay, Volkan
Abstract : BACKGROUND: The cytologic features of undifferentiated pancreatic carcinoma with osteoclastic giant cells (UOC) are rarely described. METHODS: Cytologic and clinicopathologic characteristics in 15 UOC fine‐needle aspiration (FNA) specimens were analyzed. RESULTS: FNA specimens were obtained from 6 men and 8 women with a mean age of 65 years who had UOCs (head, n = 7; body, n = 3; and tail, n = 4) with a mean radiologic size 7.3 cm, and some had a cystic component (n = 9). Three cell types (osteoclastic giant cells, pleomorphic tumor giant cells, and spindled/histiocytoid cells) were observed in 12 of 15 specimens (80%); and pancreatic ductal adenocarcinoma (PDAC) was present in 11 specimens. FNA diagnoses were UOC (n = 6), PDAC (n = 5), poorly differentiated carcinoma (n = 2), "suspicious for neoplasm" (n = 1), and "negative" (n = 1). Five of 5 specimens with osteoclastic giant cells were positive for cluster of differentiation 68 (CD68) (a glycoprotein that binds to low‐density lipoprotein). Pleomorphic tumor giant cells and spindled/histiocytoid cells were positive for pancytokeratin (6 of 7 specimens), CAM5.2 (2 of 3 specimens), and epithelial membrane antigen (2 of 2 specimens). INI‐1 protein expression was retained in 3 of 3 specimens. The Ki‐67 labeling index was assessed in 3 specimens and was 12%, 18%, and 40%; 4 of 12 resected UOCs were pure, and 8 were mixed with PDAC. One resection specimen had intraductal papillary mucinous neoplasm, and 2 had mucinous cystic neoplasms. The median overall survival (OS) of patients who had UOCs identified on FNA was 8 months (6 died [OS, 8 months; range, 2‐22 months], and 8 remained alive [OS, 3 months; range, 1‐27 months]), which was similar to the survival of 74 patients who had PDACs identified on FNA (OS, 15 months; P = .279) but worse than that of the 27 patients with UOCs who did not undergo FNA (OS, 92 months; P = .0135). CONCLUSIONS: The 3 classical UOC cell types are identifiable on FNA, making cytologic diagnosis possible if considered in the differential. A PDAC component is often also observed. The survival advantage of UOC over pure PDAC appears to be negated by FNA and requires further investigation. Cancer Cytopathol 2017;125:563–75 . © 2017 American Cancer Society . Abstract : Undifferentiated pancreatic carcinoma with osteoclastic giant cells is a rare malignant tumor that is typically large, frequently has a ductal component, and exhibits 3 classical cell types, including benign osteoclastic giant cells, malignant pleomorphic giant cells, and spindled/histiocytoid tumor cells, making cytologic diagnosis possible in most cases.